PROFIL KLT-BIOAUTOGRAFI DAN DENSITOMETRI SENYAWA TERAKTIF (ISOLAT KP13) DARI RIZOSFER KAYU PUTIH - Alfian Syarifuddin; Nanik Sulistyani; Kintoko - (Universitas Muhammadiyah Magelang, 2019)
The rate of infection, especially in Indonesia is still high. Treatment of infections by using antibiotics is constrained by cases of resistance to antibiotics so that it is necessary to explore microorganisms that can produce antibiotics. Antibiotics produced by KP13 bacterial isolates have the potential as antibiotics against Escherichia coli. The purpose of this study was to determine the TLC-Bioautography profile and Densitometry analysis of the most active fraction of KP13 bacterial isolates which have the potential as antibiotics against Escherichia coli bacteria. TLC using the mobile phase Chloroform: Ethylacetate: Methanol (4: 1: 0.5). Active compounds were analyzed using GC-MS. The results showed active spots during TLC-Biaoautography with a Rf value of 0.78. Compounds that are thought to be responsible for antibiotic activity detected by GC-MS at a Rf value of 0.78 have similarities with the compounds of cycloheptatriene and tetrahydrophyran..